THE INFLUENCE OF INSTAGRAM SOCIAL MEDIA PROMOTION AND TOURIST ATTRACTION ON DECISION TO VISIT PANTJORAN PIK, NORTH JAKARTA - Rina Fitriana; Heru Suheryadi (Jurnal Scientia, 2023)
This research aims to analyze the influence of Instagram social media promotion and the attractiveness of the Pantjoran PIK North Jakarta tourist destination on the decision to visit. The research methodology employed a quantitative approach using SPSS Version 24. The population of the study consisted of students from the Trisakti School of Tourism who had previously visited Pantjoran PIK, with a total sample of 100 respondents. The sampling technique used was simple random sampling. The research questions formulated in this study are: How does Instagram social media promotion and the attractiveness of the tourist destination influence the decision to visit Pantjoran PIK? The research findings indicate that: 1) Social Media Promotion (X1) on Instagram for Pantjoran PIK has an influence on the Decision to Visit (Y). 2) Tourist Attraction (X2) has an influence on the Decision to Visit (Y). 3) Social Media Promotion (X1) and Tourist Attraction (X2) have an influence on the Decision to Visit (Y).